Oprogramowania oparte na sztucznej inteligencji w sądach na całym świecie: praktyka, perspektywy i wyzwania mające znaczenie dla Węgier i Europy Środkowej - Kálmán, Kinga; Kiss, Laura Olga; Mezei, Kitti; Szentgáli-Tóth, Boldizsár (Wydawnictwo C.H. Beck, 2022)
In recent years, in the field of science there have been debates on the possibility of applying Artificial Intelligence in courts with participants from any discipline. And so it is in Hungary. However, adversarial views are stuck on the level of generalizations based on a theoretical square one, and legal science has not done a lot regarding the issue, mainly because of the lack of specific practical experience. In the present article, after the report on the current situation in Hungary, the authors will analyze which solutions are already in force abroad and what can be said about their effectiveness and influence on the procedures. The purpose is to put flesh on the modern technology, which is Artificial Intelligence-based software, to the readers, and active judges, representatives of legal professions, and also anyone who is currently looking for legal advice, or will do so in the future, or those who are interested in the future shape of courts. Such a seemingly distant process is not going to omit neither Hungary nor the whole region, therefore, it is crucial to address this modern branch of technology in courts.
Keywords: sztuczna inteligencja w zastosowaniu sądowym; innowacje sądowe; cyfryzacja sądów; zautomatyzowane podejmowanie decyzji; przełomowa technologia; sąd informatyzacji; AI; oprogramowanie oparte na sztucznej inteligencji; sąd online